جمود بطور وجوہِ زوالِ ِاُمتِ مسلمہ:فکرِ اقبال کی روشنی میں: Stagnation as a Cause of the Decline of the Muslim Ummah: In the Light of Iqbal’s Thought (Research Journal Tahqeeqat, 2025)
This abstract deals with the critical view of Allama Muhammad on Stagnation (intellectual and spiritual rigidity) and the role it plays in the downfall of Muslim Ummah. Allama Iqbal  strongly opposed stagnation, which according to him is related with blind imitation(taqlid),loss of creative thinking and detatchment from dynamic spirit of Islam,stagnation paralyzes individual and collective will, suppresses Khudi (selfhood), and societies fail to respond to changing historical and intellectual challenges of modern era, Iqbal's critique of stagnation is of great relevance in present day as Muslim societies are still facing the challenges of intellectual inaction and cultural complacency. By revive the principles of Khudi, creative intellect, and moral courage Iqbal provides a framework of transformation for overcoming stagnation and attaining renewal and progress.